Firm-specific and macroeconomic determinants of commercial banks liquidity in Ethiopia: Panel data approach - Mekonnen Kumlachew Yitayaw (Cogent Business & Management, 2021)
This study investigated the bank-specific and macroeconomic determinants of commercial banks' liquidity in Ethiopia using secondary unbalanced panel data. The empirical analysis is carried out through the use of the generalized method of moments (GMM) estimation of dynamic panel data from 15 commercial banks from 2009-2019. The model result shows that lagged value of liquidity and deposit had a positive and statistically significant effect on commercial banks' liquidity. On the other hand, capital adequacy, bank size, interest rate margin, and gross domestic product had a negative and statistically significant effect on the commercial bank's liquidity. The study suggested that commercial banks in Ethiopia shall be more concerned about deposit mobilization to maintain a sufficient liquidity buffer and improve liquidity performance. Finally, the current study provides useful insights for bankers, analysts, regulators, investors, and other interested parties on the liquidity levels of Ethiopian commercial banks and their determinants and contributes to the scarce empirical evidence.
Keywords: 650; Environmental Economics; Business; Management and Accounting; Industry & Industrial Studies